Exploring the Nature of the Elderly People Life Style: A Grounded Theory - Abolfazl Rahimi; Monireh Anosheh; Fazlollah Ahmadi; Mahshid Foroughan (University of Social Welfare & Rehabilitation Sciences, 2016)
Objectives: Our community which is walking into aging, is facing with various health care problems. Existing evidence has shown that the major cause of many mortalities is the unhealthy life styles, which are worsen with aging and senility, causing many problems in old age. Due to the importance of prevention of risk factors and continual caring of the elderly, as well as few studies done in Iran on elderly life styles with qualitative method, the current study was conducted aiming at clarifying the concept, structure, and nature of choosing life styles among Iranian elderly population. Methods & Materials: To achieve the objectives of this study, a qualitative research was performed according to grounded theory. We attemptted to explore the concept, structure, nature, and process of choosing life styles among the elderly population, by purposeful sampling at first and then by theoretical sampling until data saturation achieved. Unstructured interview was used for data collection. Participants of this study were elderly people (living with their families). In total, 29 in-depth individual interviews were done with 23 male and female participants. Collected data were transcript immediately and analysis was done using Strauss and Corbin approach (1998). Results: The following 8 main categories were emerged from the data analysis: aging restrictions, daily living behaviors, unsuitable sociofamilial structure, self-management, health deficits, insufficient efficacy, insufficient readiness, and sprituality. Category of daily living behaviors represented phenomenon, self-management displayed measures taken by individuals and the category of health deficits was the consequence of these strategies. Conclusion: According to the consequences of the strategies adopted and based on health definitions, it could be argued that older people do not have a perfect healthy life style and their health is deficient. Based on the results of grounded theory, correction and promotion of unhealthy life style behaviors are considered essential.